Treatment-resistant schizophrenia: current insights on the pharmacogenomics of antipsychotics - Lally J; Gaughran F; Timms P; Curran SR (Dove Medical Press, 2016)
John Lally,1–3 Fiona Gaughran,1,3 Philip Timms,4,5 Sarah R Curran5–7 1Department of Psychosis Studies, Institute of Psychiatry, Psychology and Neuroscience, King’s College London, London, UK; 2Department of Psychiatry, Royal College of Surgeons in Ireland, Beaumont Hospital, Dublin, Ireland; 3National Psychosis Service, 4START Team, South London and Maudsley NHS Foundation Trust, 5King’s College London, 6South West London and St George’s Mental Health NHS Foundation Trust, 7St George’s University of London, London, UK Abstract: Up to 30% of people with schizophrenia do not respond to two (or more) trials of dopaminergic antipsychotics. They are said to have treatment-resistant schizophrenia (TRS). Clozapine is still the only effective treatment for TRS, although it is underused in clinical practice. Initial use is delayed, it can be hard for patients to tolerate, and clinicians can be uncertain as to when to use it. What if, at the start of treatment, we could identify those patients likely to respond to clozapine – and those likely to suffer adverse effects? It is likely that clinicians would feel less inhibited about using it, allowing clozapine to be used earlier and more appropriately. Genetic testing holds out the tantalizing possibility of being able to do just this, and hence the vital importance of pharmacogenomic studies. These can potentially identify genetic markers for both tolerance of and vulnerability to clozapine. We aim to summarize progress so far, possible clinical applications, limitations to the evidence, and problems in applying these findings to the management of TRS. Pharmacogenomic studies of clozapine response and tolerability have produced conflicting results. These are due, at least in part, to significant differences in the patient groups studied. The use of clinical pharmacogenomic testing – to personalize clozapine treatment and identify patients at high risk of treatment failure or of adverse events – has moved closer over the last 20 years. However, to develop such testing that could be used clinically will require larger, multicenter, prospective studies. Keywords: personalized medicine, pharmacogenetics, treatment resistant psychosis, clozapine, pharmacokinetic, pharmacodynamic